Retrosynthesis Strategy in Organic Chemistry - Fawwaz, Muammar (Pharmaceutical Reports, 2025)
Retrosynthetic analysis represents a cornerstone of modern organic synthesis, providing a rational and highly systematic framework for the design and planning of complex molecular architectures. This strategy involves the stepwise disconnection of a target molecule into progressively simpler intermediates and ultimately into commercially available or readily accessible starting materials. By focusing on strategic bond disconnections and functional group interconversions, retrosynthesis facilitates the identification of key synthetic transformations, allowing chemists to navigate backward from the desired product to a feasible synthetic route. The integration of this methodology enables the optimization of reaction sequences in terms of step economy, atom economy, stereoselectivity, and overall synthetic efficiency. Furthermore, retrosynthetic planning is indispensable in the synthesis of biologically active compounds, natural products, and pharmaceutical agents, where the construction of complex frameworks demands both creativity and precision. As such, retrosynthesis not only streamlines the synthetic process but also enhances the reliability, scalability, and reproducibility of organic synthesis, making it an essential tool in both academic research and industrial applications.